First records of Aleiodes wesmael, 1838 species in East Marmara region of Turkey (Hymenoptera: Braconidae: Rogadinae) - Aydogdu, M. (Acta entomologica slovenica (Ljubljana), 2006)
Collecting was carried out in spring, summer and autumn periods from 1992 to 2002 in a wide range of habitats at different altitudes in the East Marmara Region of Turkey. 14 species of the genus Aleoides Wesmael, 1838 were determined. Four species are reported for the first time in the Turkish fauna.The general distribution and known hosts of the taxa are added.
Keywords: entomologija; favna; insekti; Turčija; Turkey